Auto-Tuning Methodology to Represent Landform Attributes on Multicore and Multi-GPU Systems - Boratto, Murilo; Alonso, Pedro; Giménez, Domingo (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2012)
Auto-Tuning techniques have been used in the design of routines in recent years. The goal is to develop routines which automatically adapt to the conditions of the computational system, in such a way that efficient executions are obtained independently of the user's experience. This paper aims to explore programming routines that can be automatically adapted to the computational system conditions, making possible to use Auto-Tuning methodology to represent landform attributes on multicores and multi-GPU systems.